A study on psychological modelling of market maven for marketing operations with special reference to Indian market. (1st January 2014) - Harikrishnan, K.; Ashok, D.; Dominic, P.D.D.; Anand, S. Joseph Jeya
In this era of intense commercial information bombardment, the interpersonal communication 'word of mouth' (WOM) cuts through the clutter, and gains importance among consumers. Market maven plays a pivotal role in providing valuable market place information through WOM and thereby helping consumers towards their purchases. Literatures indicated need for profiling market mavens with psychological factors, hence the authors hypothesised and tested structural equation model with consumer innovativeness, consumers' need for uniqueness-creative choice counter conformity-dimension, status consumption as exogenous, antecedent constructs, market maveness as endogenous construct and market helping behaviour-information provided-dimension as an ultimate endogenous, consequence construct, this model was not tested by earlier studies. The structural equation modelling (SEM) results indicated the hypothesised model was consistent with data and the psychological antecedent constructs were having positive relationship with market mavenness. Market mavenness was found to have positive relationship with consequence construct market helping behaviour-information provided-dimension. The findings of this study will enhance the marketers' ability, leveraging on findings about market mavens, to evolve an effective marketing programme.